The value of DCE-MRI in assessing histopathological and molecular biological features in induced rat epithelial ovarian carcinomas - Su Juan Yuan; Tian Kui Qiao; Jin Wei Qiang; Song Qi Cai; Ruo Kun Li (BMC, 2017)
Abstract Background To investigate dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) for assessing histopathological and molecular biological features in induced rat epithelial ovarian carcinomas (EOCs). Methods 7,12-dimethylbenz[A]anthracene (DMBA) was applied to induce EOCs in situ in 46 SD rats. Conventional MRI and DCE-MRI were performed to evaluate the morphology and perfusion features of the tumors, including the time-signal intensity curve (TIC), volume transfer constant (Ktrans), rate constant (Kep), extravascular extracellular space volume ratio (Ve) and initial area under the curve (IAUC). DCE-MRI parameters were correlated with histological grade, microvascular density (MVD), vascular endothelial growth factor (VEGF) and fraction of Ki67-positive cells and the serum level of cancer antigen 125 (CA125). Results Thirty-five of the 46 rats developed EOCs. DCE-MRI showed type III TIC more frequently than type II (29/35 vs. 6/35, p < 0.001) in EOCs. The two types of TIC of tumors had significant differences in the histological grade, MVD, expression of VEGF and Ki67, and the serum level of CA125 (all p < 0.01). Ktrans, Kep and IAUC values showed significant differences in different histological grades in overall and pairwise comparisons except for IAUC in grade 2 vs. grade 3 (all p < 0.01). There was no significant difference in Ve values among the three grade groups (p > 0.05). Ktrans, Kep and IAUC values were positively correlated with MVD, VEGF and Ki67 expression (all p < 0.01). Ve was not significantly correlated with MVD, VEGF expression, Ki67 expression and the CA125 level (all p > 0.05). Conclusions TIC types and perfusion parameters of DCE-MRI can reflect tumor grade, angiogenesis and cell proliferation to some extent, thereby helping treatment planning and predicting prognosis.